Implementación de una solución web y móvil para la gestión vehicular basada en Arquitectura de Aspectos y metodologías ágiles: Un enfoque educativo de la teoría a la práctica - Quezada- Sarmiento, Pablo Alejandro; Andrés, Santiago Mengual (RISTI : Revista Ibérica de Sistemas e Tecnologias de Informação, 2017)
Palabras Clave: Aplicativo web; Educación; ICONIX; POA, Metodología Abstract: In this article, the analysis, application of agile methodologies, and technologies open source used in the development of a web and mobile application, to automated, and control the automotive fleet of the Technical University of Loja (UTPL) it was detailed; this application it was development by educational component of Web Programming in the Affective Computational Project. Within the essential functions of the web application is the management of vehicles that involved registration: fuel and maintenance orders, invoices, suppliers, drivers and vehicles; In addition to the management of vehicle loans that involved the registration of applications, inputs, outputs and vehicle status. Once the web application has been implemented, users and the administrator will have the ability to access all the services that it presents in an interactive and truthful way, helping to better control, management and usability based on the time and place where the people requires it. EMG signal patterns recognition based on feedforward artificial neural network applied to robotic prosthesis myoelectric control.